Politik Identitas Komunitas Bali di Desa Mukti Jaya Kecamatan Muara Telang Kabupaten Banyuasin - Indah Sari; Endang Rochmiatun (Ampera: A Research Journal on Politics and Islamic Civilization, 2020)
This paper explains and depicts the Politics of Bali Community Identity in the Mukti Jaya Village, Muara Telang District, Banyuasin District. This type of research is a study using a fact-based field case study approach in the field. The focus of this study is to find out how the Balinese group can be accepted and mingled, and even the existence of other migrant populations is recognized without social and cultural discrimination. This research wanted to know what processes and actions carried out by the Balinese group in order to get recognition and get their rights to be equal with other residents, and how the approach of the Balinese group with the majority community so that they never experienced conflict can live side by side safely and peacefully. In the village of Mukti Jaya, the Balinese group established very good relations with other migrants, the Balinese group upheld tolerance and help other fellow migrants. even the Balinese group was once the leader of a village head in the village of Mukti Jaya, with the holding of Balinese as the head of the Mukti Jaya Village the first milestone in getting permission to establish a place of worship in the village of Mukti Jaya. Balinese ethnic customs still flourish in the village of Mukti Jaya, and are still taught to the young generation of Balinese. for example Ogoh-ogoh celebrations, Ngaben ceremonies, and other Balinese arts.